Analisis Rasio Pertumbuhan dan Keserasian pada Pemerintah Provinsi Sumatera Utara - Ferica Christinawati Putri (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Budget Realization Reports (LRA) published by local governments as a form of local government accountability in providing information that is very useful for users of regional financial information to assess regional financial performance. LRA is one of the main regional financial accountability reports. Regional spending reflects local government policies and the direction of regional development. The object of research is the Provincial Government of North Sumatra. The aim of the study was to analyze the performance of regional spending based on the ratio of growth and compatibility in the Budget Realization Report (LRA) for the North Sumatra Provincial Government for the 2020-2021 fiscal year. The analytical method used is descriptive analysis method which is carried out by making a description of the problems that have been identified. From the results of the analysis which consists of analysis using the ratio of growth and compatibility shows the existence of spending growth. Expenditure that most influenced the increase in expenditure growth was Goods and Services Expenditure and the direction of regional development oriented to the performance of DKI Jakarta Provincial Government expenditure on operational activities rather than capital expenditure activities.